Profiling of the Beneficial and Potentially Harmful Components of Trichodesma indicum Seed and Seed Oil Obtained by Ultrasound‐Assisted Extraction. (17th January 2019) - Górnaś, Paweł; Picron, Jean‐François; Perkons, Ingus; Mišina, Inga; Rudzińska, Magdalena; Sobieszczańska, Natalia; Chakradhari, Suryakant; Patel, Khageshwar Singh
Abstract: The beneficial and potentially harmful bioactive components in the seeds and seed oil of Trichodesma indicum L. (Boraginaceae) were investigated in the present study. The T. indicum seeds were rich in oil (29.0%), phenolic compounds (PC, 1881.2 mg per 100 g), and pyrrolizidine alkaloids (PA, 2, 702, 338 ng g −1 ). Seven PC were identified in T. indicum seeds by liquid chromatography‐quadrupole‐time‐of‐flight mass spectrometry system (LC‐Q‐TOF‐MS). Rosmarinic acid (67%) and isomers of salvianolic acid B/E/L (26%) were the main phenolics, while melitric acid A and sebestenoid C/D constituted 6% and 1%, respectively. Only a minor part of the total PC and PA was transferred from the seeds into the oil fraction during the extraction procedure (<0.03%). The T. indicum seed oil was predominated by the following polyunsaturated fatty acids (PUFA):linoleic (23.2%), γ‐linolenic (6.0%), α‐linolenic (26.8%), and stearidonic (5.9%). High levels were also observed for oleic (26.7%) and palmitic (7.4%) acids. Additionally, notable amounts of γ‐tocopherol (92% of total tocochromanols) and β‐sitosterol (53% of total sterols) were found in T. indicum seed oil. The total content of tocochromanols, sterols, and carotenoids in T. indicum seed oil was 102.7, 236.0, and 0.6 mg per 100 g oil, respectively. Among 10 detected hepatotoxic PA in T. indicum seeds, intermedine/lycopsamine/indicine (90.9%), intermedine N‐oxide (4.9%), and lycopsamine N‐oxide (4.1%) consisted 99.9% of the total PA concentration. The T. indicum seeds should be used carefully due to the presence of PA.